2012
DOI: 10.7314/apjcp.2012.13.10.5037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tobacco on Glutathione S Transferase Gene Loci of Indian Ethnics

Abstract: Background: Tobacco contains agents which generate various potent DNA adducts that can cause gene mutations. Production of DNA adducts may be neutralized by glutathione S transferase (GST) along with other phase I and phase II enzyme systems. The existence of null type of GST among the population increases the susceptibility to various disorders and diseases. The present study focuses on the impact of high tobacco usage and possible null type mutation in GST loci. Methods: Genotypes of GST were detected by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the genotype frequencies of Glo1 polymorphism were deviating from HardyWeinberg equilibrium (X 2 = 39.62 and p = 0.5 for type 1; X 2 = 54.42 and p = 0.56 for type 2 diabetes) [ 25 ] . This, for example, could be due to recent somatic mutations, which have not attained null alleles [ 26 ] . In addition, only Caucasian subjects were enrolled while no other genetic background was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the genotype frequencies of Glo1 polymorphism were deviating from HardyWeinberg equilibrium (X 2 = 39.62 and p = 0.5 for type 1; X 2 = 54.42 and p = 0.56 for type 2 diabetes) [ 25 ] . This, for example, could be due to recent somatic mutations, which have not attained null alleles [ 26 ] . In addition, only Caucasian subjects were enrolled while no other genetic background was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We found no association of GSTP1 variant genotypes with colorectal cancer risk (OR=1.077, 95% CI: 0.580−1.999). On contrary, other studies reported a significant association between GSTP1 variant genotypes and colorectal cancer risk (Kassab et al, 2014;Lalosevic et al, 2019;Matakova et al, 2009;Senthilkumar and Thirumurugan, 2012;Wang et al, 2011). While Hezova et al (2012) have reported a decreased risk of GSTP1 heterozygote genotype (Ile105Val) and association with colorectal cancer (Hezova et al, 2012).…”
Section: Discussionmentioning
confidence: 91%